2020
DOI: 10.1101/2020.09.14.20193987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Death associated with coronavirus (COVID-19) infection in individuals with severe mental disorders in Sweden during the early months of the outbreak – a exploratory cross-sectional analysis of a population-based register study

Abstract: Background: Individuals with severe mental disorder (SMD) have a higher risk of somatic comorbidity and mortality than the rest of the population. We set up a population-based study to assess whether individuals with SMD had a higher risk of death associated with a COVID-19 infection (COVID-19 associated death) than individuals without SMD. Methods: Exploratory analysis with a cross-sectional design in the framework of a population-based register study covering the entire Swedish population. The Swedish Board… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
3
13
0
2
Order By: Relevance
“…38 Arguably, the increased risk of worse COVID-19-related outcomes in people with psychiatric disorders, and especially in those with severe mental illness, is due to frequent comorbidity with physical diseases related to poor COVID-19 outcomes. However, the aforementioned Personal View studies [17][18][19][20][21][22][23] showed a risk greater than that of physical diseases by correcting for them in the analyses. Therefore, psychiatric disorders confer an additional risk for SARS-CoV-2 infection and COVID-19-related morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Arguably, the increased risk of worse COVID-19-related outcomes in people with psychiatric disorders, and especially in those with severe mental illness, is due to frequent comorbidity with physical diseases related to poor COVID-19 outcomes. However, the aforementioned Personal View studies [17][18][19][20][21][22][23] showed a risk greater than that of physical diseases by correcting for them in the analyses. Therefore, psychiatric disorders confer an additional risk for SARS-CoV-2 infection and COVID-19-related morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…7 Several studies have found an association between an existing psychiatric disorder and increased risk for SARS-CoV-2 infection and COVID-19-related hospitalisation, morbidity, and mortality. [17][18][19][20][21][22][23][24] Some of these studies also specifically examined the difference between risks associated with severe mental illness, as described by diagnosis, severity, or previous hospitalisation for a mental disorder, and other psychiatric disorders. These studies point to a higher risk for worse COVID-19-related outcomes for people with severe mental illness than for people with less severe mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…We gratefully acknowledge Olga Filson for her assistance with the data analysis. This manuscript has been released as a pre-print at medRxiv ( 73 ).…”
mentioning
confidence: 99%
“…[27][28][29][30] People with major mental illnesses are more likely to become infected with COVID-19 in the community and are more than twice as likely to have a severe outcome from COVID-19 infection than the general population. [31][32][33] Outbreaks have occurred worldwide in psychiatric centres, including forensic hospitals, with fatal results. 1,2 High transmission rates have been found within psychiatric units despite implementation of Centers for Disease Control and Prevention (CDC) guidelines.…”
Section: Vulnerable Groups and Vulnerable Settingsmentioning
confidence: 99%